Meth abuse and oral health - Deviprasad Makonahally; Vaibhav Gupta; Pushpanjali Krishnappa (Wolters Kluwer Medknow Publications, 2015)
Methamphetamine abuse is spreading its roots in India due to its widespread appeal, ease of manufacture and low cost compared with other stimulant drugs. Methamphetamine-induced caries is a characteristic finding among methamphetamine abusers. Thus, it is important to understand the typical clinical manifestations inclusive of cervical and proximal caries, elicit proper case history and develop a comprehensive treatment plan to help patients in a complete rehabilitation. We present a series of cases of "meth" abuser for dental professionals to help ensure successful treatment and prevention of disease progression.